Advances in Plant Biopesticides 2014
DOI: 10.1007/978-81-322-2006-0_15
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Pesticides

Abstract: Many phytochemical pesticides exhibiting broad spectrum of activity against pests and diseases have long been considered as attractive alternative to synthetic chemical pesticides as they are biodegradable, target specifi c, and pose no or less hazard to the environment or to human health. Although a large number of studies suggest that plant-based materials do affect arthropod pests, vectors, and other pathogens, yet only a handful of botanicals are currently used in agriculture, and there are few prospects f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 202 publications
(131 reference statements)
0
8
0
Order By: Relevance
“…Previous studies have already reported more than 2500 plant species belonging to 235 families, which have demonstrated their biological activity against several types of pests [ 1 ]. However, in spite of the remarkable potential as natural sources for commercial botanical pesticide development, not many have been found on the market, remaining in use only for small organic crops and commonly classified as so-called farming products [ 106 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have already reported more than 2500 plant species belonging to 235 families, which have demonstrated their biological activity against several types of pests [ 1 ]. However, in spite of the remarkable potential as natural sources for commercial botanical pesticide development, not many have been found on the market, remaining in use only for small organic crops and commonly classified as so-called farming products [ 106 ].…”
Section: Discussionmentioning
confidence: 99%
“…The action of soaps on the wax covering of insects is influenced by the temperature [ 64 ]. Additionally, the crude oils may also act by interfering with insect respiration by plugging the orifices called spiracles, resulting in death by asphyxiation, controlling several types of insects such as whiteflies, mites, caterpillars, leafhoppers and beetles [ 1 ].…”
Section: Plant Derived Insecticides That Affect the Water Balancementioning
confidence: 99%
See 2 more Smart Citations
“…Besides, the pressing scientific and social necessities to Open Access *Correspondence: sayed_zahran2000@yahoo.com; elsayed.ramadan@eaea.org.eg develop safe, cheap, and eco-friendly alternatives to avoid hazards resulting from the excessive use of synthetic pesticides (Manu et al 2021). Over the years, the use of phyto-chemicals as pesticides were extensively studied (Ali et al 2021) with the result of the identification of several leads from a wide range of plant species (Walia et al 2014). Although, plants proved to be a rich source of natural compounds for insect control, the very low yields and unsustainable supply were the main drawbacks (Molyneux et al 2007).…”
Section: Introductionmentioning
confidence: 99%